INTERNATIONAL AND NATIONAL STANDARDS FOR PROTECTION AND TREATMENT OF UNACCOMPANIED MINORS - Dimitrijoska, Sunchica; Dimitrijevikj, Srboljub D. (Ревија за социјална политика/Journal of Social Policy, 2016)
The issue of unaccompanied children is not new, although in the recent period, this topic has been discussed frequently, taking in consideration the growing number of children at the margins of the global society, being exposed to serious forms of abuse and exploitation.In practice, we come across and we identify the unescorted children, most frequently as: smuggled migrants, victims of human trafficking, asylum seekers, foreign juvenile citizens that legally entered in the country and were left without escort on the territory of the Republic of Macedonia. The main subject of this analysis is as follows: defining unaccompanied children deiure and defacto, and defining standards for protection of this category of children who as a result oftheir vulnerable situation become objects exploitation of highly organized criminal groups. Internationally and nationally there isn’t much statistical data, academic publications, research papers and other sources of information that research the issue of unaccompanied children. This analysis aims primarily to open the issue of unaccompanied children and the degree of their vulnerability, to elaborate the existing national and international legislation and the protection procedures that exist in the country,and to provide recommendations for promotion of the system for protection of unaccompanied children and to provide guidelines for complying national legislation with international standards wherever required.